Jack Bean (Canavalia ensiformis) Tempeh: ACE-Inhibitory Peptide Formation during Absorption in the Small Intestine - Puspitojati, Endah; Cahyanto, Muhammad Nur; Marsono, Yustinus; Indrati, Retno (University of Zagreb, 2023)
Research background. High blood pressure is the most significant cause of mortality globally. Some fermented foods include ACE-inhibitory peptides that help fight this dis-ease. The ability of fermented jack bean (tempeh) to inhibit ACE during consumption has not been demonstrated yet. This study identified and characterised ACE-inhibitory peptides from jack bean tempeh produced by small intestine absorption using the everted intestinal sac model. Experimental approach. Sequentially, the protein extract of jack bean tempeh and un-fermented jack bean was hydrolysed using pepsin-pancreatin for 240 min. The hydrolysed samples were then evaluated for the peptide absorption using three-segmented everted intestinal sacs (duodenum, jejunum and ileum). The peptides absorbed from all intestinal segments were mixed in the small intestine. Results and conclusions. The data showed that both jack bean tempeh and unferment-ed jack bean had the same peptide absorption pattern, with the highest percentage of peptide absorption in the jejunum, followed by the duodenum and ileum. The absorbed peptides of jack bean tempeh exhibited equally strong activity of ACE inhibition in all intestinal segments, while the unfermented jack bean showed strong activity only in the jejunum. The mixture of the peptides from jack bean tempeh absorbed in the small intestine had higher ACE-inhibitory activity (81.09 ) than the unfermented jack bean (72.22 ). The peptides produced from jack bean tempeh were identified as pro-drug ACE inhib-itors and had the mixed inhibition pattern. The mixture of peptides consisted of seven types of peptides with a molecular mass of 826.86â978.20 Da (DLGKAPIN, GKGRFVYG, PF-MRWR, DKDHAEI, LAHLYEPS, KIKHPEVK, and LLRDTCK). Novelty and scientific contribution. This study discovered that consuming jack bean tempeh generated more potent ACE-inhibitory peptides during small intestine absorption than cooked jack beans. Absorbed tempeh peptides have high ACE-inhibitory activ-ity. Â© 2023, University of Zagreb. All rights reserved.